The analytical performance of Saccharomyces cerevisiae and Bacillus megaterium microbial consortium as recognition element in ethanol biosensor - NURDIANI NURDIANI; DYAH ISWANTINI; NOVIK NURHIDAYAT; WULAN TRI WAHYUNI; AGUS KARTONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nurdiani, Iswantini D, Nurhidayat N, Wahyuni WT, Kartono A. 2023. The analytical performance of Saccharomyces cerevisiae and Bacillus megaterium microbial consortium as recognition element in ethanol biosensor. Biodiversitas 24: 5928-5936. Alcohol, particularly ethanol, is commonly found in human food and plays a significant role in degenerative diseases and disability. Accurate measurement of alcohol in food products is essential to ensure adherence to the Muslim halal rule. However, existing alcohol biosensor that relies on a single microbe has limitations in measuring a wide range of ethanol concentrations. To address this issue, a microbial consortium is needed to expand the measurable range. Therefore, this study aimed to develop an innovative biosensor to widen the range of measured ethanol concentrations based on the microbial consortium of Saccharomyces cerevisiae YSAPMI.2 and Bacillus megaterium BSAPMI.1. The performance of the biosensor was evaluated using the cyclic voltammetry method. The results showed that the linear range, linearity, coefficient of determination, sensitivity, and response time, were 0.02-6.0%, 0.9968, 0.9936, 83.157 µA (%)-1, and 11 seconds. The LoD ??and LoQ theoretical values ??of the method obtained in the ethanol oxidation reaction were 0.060% and 0.182%, respectively. The confirmatory test for the LoD value of 0.01% yielded a positive response, while the confirmed LoQ value of 0.02% showed good precision and accuracy. The biosensor had precise %RSD values of 0.568, 1.338, and 4.632% for the high, medium, and low ethanol concentrations, respectively. The accuracy reflected as the recovery percentage was in the range of 90.27-111.07%. The biosensor was relatively specific and had no interferences with common ethanol compounds including methanol, sodium chloride, formic acid, and glucose. The stability obtained with biofilm showed a better result reaching 88% in 70 days. Based on the result, this microbial consortium biosensor could widen the range of measured ethanol concentrations and should be further developed to create a prototype for an accurate and practical analysis.